The Performance of the U Shape Double pipe heat exchanger under effect of using Active Techniques. - Muhamad F. Albayati; Rafeq A. Khalefa (NTU Journal of Engineering and Technology)
The main aim from this research experimentally studied the effect of  external power effect like use the active technique which is represented as an air bubble injection on shell side of of U shape double pipe heat exchanger and in this  investigations was used a suitable U shape heat exchanger with different position  angle of the U shape Exchanger like position (U shape , ? Inverse U shape ) in additionally used a system which  has all the equipments  that measuring flow rates and parameters, the vortex generation due to the curvature of bending shell and tube has strong effect to increase the performance of exchanger.  The results with this injection inside the shell side demonstrated  that the optimize position of exchanger with best  performance of  parameter was with (?) Inverse and the exchanger enhancement was (24.4%) due to the different shape of diffuser which was used it with inverse U shape exchanger. the air bubble injection as active technique it suggested that the effect cause by the bubble increment the agitation of flow  and due to the motion of fluid and air as mixing turbulence flow motion and  increased the heat transfer rate and performance  parameter of exchanger .